Development of Entrustable Professional Activities and Standards in Training in Pediatric Neurogastroenterology and Motility: North American Society for Pediatric Gastroenterology, Hepatology and Nutrition and American Neurogastroenterology and Motility Society Position Paper. Issue 1 (January 2021) - Khlevner, Julie; Rosen, Rachel; Ambartsumyan, Lusine; Lusman, Sarah Shrager; Rosen, John M.; Yacob, Desale; Mousa, Hayat; Nurko, Samuel; Di Lorenzo, Carlo; Boruta, Mary; Ratcliffe, Elyanne M.; Feinstein, Laurence; et al.
Abstract : ABSTRACT: Neurogastroenterology and motility (NGM) disorders are common in childhood and are often very debilitating. Although pediatric gastroenterology fellows are expected to obtain training in the diagnosis and management of patients with these disorders, there is an ongoing concern for unmet needs and lack of exposure and standardized curriculum. In the context of tailoring training components, outcome and expressed needs of pediatric gastroenterology fellows and programs, members of the North American Society for Pediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN) and American Neurogastroenterology and Motility Society (ANMS) developed guidelines for NGM training in North America in line with specific expectations and goals of training as delineated through already established entrustable professional activities (EPAs). Members of the joint task force applied their expertise to identify the components of knowledge, skills, and management, which are expected of NGM consultants. The clinical knowledge, skills and management elements of the NGM curriculum are divided into domains based on anatomic regions including esophagus, stomach, small bowel, colon and anorectum. In addition, dedicated sections on pediatric functional gastrointestinal (GI) disorders, research and collaborative approach, role of behavioral health and surgical approaches to NGM disorders and transition from pediatric to adult neurogastroenterology are included in this document. Members of the NASPGHAN-ANMS task force anticipate that this document will serve as a resource to break existing barriers to pursuing a career in NGM and provide a framework towards uniform training expectations at 3 hierarchical tiers corresponding to EPA levels. Abstract : Supplemental Digital Content is available in the text